Association between Magnesium Disorders and Hypocalcemia following Thyroidectomy. (22nd July 2016) - Nellis, Jason C.; Tufano, Ralph P.; Gourin, Christine G.
Abstract : Objective: To identify factors associated with postoperative hypocalcemia after thyroid surgery and to understand the relationship among hypocalcemia, length of hospitalization, and costs of care. Study Design: Retrospective database analysis. Methods: Discharge data from the Nationwide Inpatient Sample for 620, 744 patients who underwent thyroid surgery from 2001 to 2010 were analyzed through cross‐tabulations and multivariate regression modeling. Hypocalcemia, length of stay, and costs were examined as dependent variables. Secondary independent variables included magnesium and phosphate metabolism disorders, vitamin D deficiency, menopause, sex, extent of surgery, malignancy, and surgeon volume. Results: Hypocalcemia was reported in 6% of patients and was significantly more common for the following variables: women, age <65 years, patients from the Northeast, total thyroidectomy ± neck dissection patients, low‐volume surgical care, malignancy, recurrent laryngeal nerve injury, and patients with disorders of magnesium or phosphate metabolism ( P <. 001). Magnesium and phosphate disorders were present in <1% of patients. Magnesium disorders were significantly more likely for patients with hypocalcemia (7%; P <. 001), and hypocalcemia was present in 52% of patients with magnesium disorders ( P <. 001). On multiple logistic regression analysis, the odds of hypocalcemia were greatest for patients with magnesium disorders (odds ratio, 12.71; 95% confidence interval, 8.59‐18.82). This relationship was not attenuated by high‐volume surgical care. Hypocalcemia and magnesium disorders were both associated with increased length of stay and costs, with a greater effect for magnesium disorders than for hypocalcemia ( P <. 001). Conclusions: Disorders of magnesium metabolism are an independent risk factor for postthyroidectomy hypocalcemia and are associated with significantly increased costs and length of stay.